TECHNOLOGY INTEGRATION IN LEARNING IN THE DIGITAL AGE: A LITERATURE REVIEW OF MODELS, CHALLENGES, AND OPPORTUNITIES - Ayu Wulandari; Eka Haryati Yuliany; Sri Parwanti (International Journal of Teaching and Learning, 2025)
This research aims to comprehensively examine the integration of technology in learning in the digital era through a literature review of emerging models, challenges and opportunities. Various integration models such as SAMR, TPACK, LoTI, blended learning, as well as the utilisation of digital platforms have been implemented to improve the effectiveness, flexibility, and relevance of learning. However, the implementation of technology in education still faces significant challenges, including limited infrastructure, access gaps, uneven digital competence, resistance to change and data security issues. On the other hand, technology integration opens up great opportunities for improving accessibility, personalising learning, global collaboration and strengthening 21st century skills. This review highlights the importance of well-planned implementation strategies, policy support and cross-stakeholder collaboration for technology integration to drive adaptive, inclusive and sustainable education transformation.